Python Data Structures Pocket Primer - Campesato, Oswald (Pocket Primer, 2022)
As part of the best-selling Pocket Primer series, this book is designed to present the fundamentals of data structures using Python. Data structures provide a means to manage huge amounts of information such as large databases and the ability to use search and sort algorithms effectively. It is intended to be a fast-paced introduction to the core concepts of Python and data structures, illustrated with numerous code samples. Companion files with source code are available for downloading. FEATURES:Begins with an introduction to Python, and covers recursion, strings, search and sort, linked lists, stacks, and moreFeatures numerous code samples throughoutIncludes companion files with source code available for downloading